Isolation And Characterization Of Nitrogen Fixing Fungi From Fruit And Vegetable Waste Compost - Dimas Prasetya, Rizki; Walida, Hilwa; Ainy Dalimunthe, Badrul; Rizal, Khairul (Publisher Cv. Inara, 2023)
Nitrogen fixing fungi are fungi capable of fixing free nitrogen into ammonium or nitrate, so that it can be absorbed by plants. Many species of microbes/fungi have the ability to fix nitrogen, but very few are able to excrete nitrogen in the form of ammonia so that their contribution in providing nitrogen for plants is also still low. This study aims to determine the characteristics and type of nitrogen fixing fungi in fruit and vegetable waste compost. The method used in this research was descriptive method. Identification of nitrogen-fixing fungi was carried out macroscopically by looking at the color of the colonies, the shape of the colonies, and the diameter of the fungal colonies, an then identified by molecularly. There were 4 isolates of nitrogen-fixing fungi capable of forming clear zones on Jensen's media with different morphological characteristics and nitrogen-fixing abilities. The largest diameter of the clear zone was shown in isolate A3 of 3.2 cm which is the fungus Aspergillus niger strain SG1.